A study on the effect of add-on rosiglitazone on the anklebrachial pressure index of patients with type 2 diabetes mellitus in hospital Universiti Sains malaysia - Mustaffa, Nazri (2007)
Background Rosiglitazone, an oral hypoglycaemic agent of the thiazolidinedione group is used for Type 2 Diabetes treatment. Research has shown that this medication, being a peroxisome proliferator activator receptor-gamma agonist has effects beyond glycaemic control alone. Apart from improving insulin resistance, the non-hypoglycaemic effects of rosiglitazone include reduction of inflammatory markers, improvement of endothelial function, improvement in fibrinolytic activity as well as changes in cholesterol profile. This study intends to see if the non-hypoglycaemic effects of rosiglitazone translate to a clinically noticable reduction in atherosclerosis as well as improvement of fibrinolytic activity. The objectives of this study were to assess changes in surrogate markers of atherosclerotic burden via ankle-brachial pressure index measurements, the number of patients who have significant peripheral artery disease in the study, changes in the diabetic prothrombotic state via serum plasminogen activity, changes in glycaemic control via HbAlc and changes in cholesterol profile by measuring total-, high density lipoprotein- and low density lipoprotein-cholesterol after rosiglitazone is added to a preexisting Type 2 Diabetes treatment regime. Methods A non-blinded cross-sectional cohort study was designed. 59 patients were enrolled. Patients who were rosiglitazone naive were prescribed 4mg of oral rosiglitazone added-on to their current medication for a period of 10 weeks. Ankle-brachial pressure index, HbAlc, serum plasminogen activity levels and fasting cholesterol profile were taken at the start and end of the study period. Patients were requested not to change their medication dose nor regime throughout the study. Results 48 out of 59 patients completed the study. Mean ankle-brachial pressure index was 1.06 ± 0.12 pre-, and 1.07 ± 0.13 post-rosiglitazone (p-value was 0.439). 4 patients (8.3%) had an ABPI ratio of less than 0.90 indicating presence of significant peripheral artery disease. Mean serum plasminogen activity (%) was 96.00 ± 14.77 before rosiglitazone, and 111.98 ± 15.83 after (p-value of 0.006). Initial mean HbAlc (%) was 9.76 ± 2.06, and second mean was 9.25 ± 2.03 (p-value was <0.001). Mean total cholesterol (mmoI/L) was 4.95 ± 1.02 before rosiglitazone and 5.32 ± 0.94 after (p=0.003). Mean high density lipoprotein cholesterol (mmollL) at the beginning was 1.32 ± 0.37 and 1.47 ± 0.41 at the end (p<O.OOl). Finally, mean low density lipoprotein cholesterol (mmoI/L) concentration was 2.89 ± 0.85 at the start and 3.08 ± 0.96 at the end (p= 0.098). Conclusion This study shows that oral rosiglitazone 4mg daily significantly improves serum plasminogen activity levels, indicating improvement in fibrinolytic activity. There is also a significant reduction in HbAlc, rise in total cholesterol as well as high density lipoprotein-cholesterol levels in line with the findings of previous studies. The rise in ankle-brachial pressure index and low density lipoprotein-cholesterol measurements however, were not significant in this study. Not many patients had significant peripheral artery disease in this study compared to previous ones before this. However, more research is needed regarding the relation between use of rosiglitazone and atheroma reduction.